Distinct HIV-1 Neutralization Potency Profiles of Ibalizumab-Based Bispecific Antibodies. (1st December 2016) - Song, Ruijiang; Pace, Craig; Seaman, Michael S.; Fang, Qing; Sun, Ming; Andrews, Chasity D.; Wu, Amos; Padte, Neal N.; Ho, David D.
Abstract : Background: Preexposure prophylaxis using antiretroviral agents has been shown to effectively prevent human immunodeficiency virus type 1 (HIV-1) acquisition in high-risk populations. However, the efficacy of these regimens is highly variable, which is thought to be largely due to the varying degrees of adherence to a daily intervention in the populations. Passive immunization using broadly neutralizing antibodies (bNAbs) against HIV-1, with their relatively long half-life and favorable safety profile, could provide an alternative to daily preexposure prophylaxis. However, most bNAbs have a limited breadth, only neutralizing 70%–90% of all HIV-1 strains. Methods: To overcome the problem of limited antiviral breadth, we proposed that targeting human CD4 and HIV-1 envelope proteins simultaneously may improve virus-neutralization breadth and potency. Therefore, we constructed bispecific antibodies (biAbs) using single-chain variable fragments of anti-gp120 bNAbs fused to ibalizumab (iMab), a humanized monoclonal antibody that binds human CD4, the primary receptor for HIV-1. Results: Some of our biAbs neutralized 100% of HIV-1 strains tested in vitro at clinically achievable concentrations. Distinct neutralization patterns were observed in this panel of biAbs. Those biAbs with specificity for the CD4-binding site on gp120 demonstrated 100% breadth, as well as slightly improved potency compared with iMab. In contrast, biAbs with specificity for the V1-V2 apex epitope or the V3-glycan epitope on gp120 demonstrated dramatically improved potency; some showed limited gain in neutralization breadth, whereas others (eg, PGT128-LM52 and 123-iMab) improved to 100% breadth. Conclusion: Our data suggest that this panel of iMab-based biAbs could be used to probe the parameters for potent HIV-1 neutralization. Moreover, a few of these biAbs warrant further studies and possibly clinical development. Abstract : Supplemental Digital Content is Available in the Text.